Seed constraint to cultivation and productivity of African indigenous leaf vegetables - O.C. Adebooye; S.A. Ajayi; J.J. Baidu-Forson; J.T. Opabode (Global Journal of Food and Agribusiness Management, 2019)
Non-availability of improved seeds constitutes a major constraint to the cultivation and productivity of the indigenous leaf vegetables (ILVs) of Africa. Research on African ILVs has focused mainly on the ethnobotany, collection, preservation, and the assessment of food value and chemical composition of the ILVs. No serious breeding and seed production research has been done on the ILVs. This paper examines some factors underlying the lack of interest in the production of ILVs seeds, the problem associated with local seed processing and the way to organize a seed production programme for the ILVs. Key Words: Seed, indigenous leaf vegetables, cultivation, production Non-availability of improved seeds constitutes a major constraint to the cultivation and productivity of the indigenous leaf vegetables (ILVs) of Africa. Research on African ILVs has focused mainly on the ethnobotany, collection, preservation, and the assessment of food value and chemical composition of the ILVs. No serious breeding and seed production research has been done on the ILVs. This paper examines some factors underlying the lack of interest in the production of ILVs seeds, the problem associated with local seed processing and the way to organize a seed production programme for the ILVs.